Peran Media Sosial Instagram Sebagai Sarana Keterbukaan Informasi Publik di Kelurahan Merjosari - Shyane Devety Natalia; Roro Merry Chornelia Wulandary (Journal of Governance Innovation, 2026)
The rapid digital transformation in the public sector has encouraged government institutions to utilize social media to enhance public information disclosure. Instagram, as one of the most widely used platforms in Indonesia, offers strategic potential to improve transparency, accessibility, and communication between governments and the community. This study aims to analyze the role of Instagram as a medium for public information disclosure in Merjosari Village. The research employed a qualitative descriptive approach, with data collected through interviews, observation, and documentation. The findings show that Instagram has been used to disseminate information related to village activities, administrative services, and policy announcements. The platform supports transparency through accessible and visually structured content and enables two-way communication through interactive features. However, its implementation has not been fully optimal due to limited human resources, the absence of standard operating procedures for social media management, and limited digital content management capacity. Overall, Instagram contributes to supporting public information disclosure at the village level.